PREPARATION OF CALCIUM OXIDE FROM Achatina fulica AS CATALYST FOR PRODUCTION OF BIODIESEL FROM WASTE COOKING OIL - Aldes Lesbani; Palita Tamba; Risfidian Mohadi; Fahmariyanti Fahmariyanti (Indonesian Journal of Chemistry, 2013)
Preparation of calcium oxide from Achatina fulica shell has been carried out systematically by decomposition for 3 h at various temperatures i.e. 600, 700, 800 and 900 °C. Formation of calcium oxide was characterized using XR diffractometer. The calcium oxide obtained with the optimum temperature decomposition was characterized using FTIR spectroscopy to indicate the functional group in the calcium oxide. The results showed that XRD pattern of materials obtained from decomposition of Achatina fulica shell at 700 °C is similar with XRD pattern of calcium oxide standard from Joint Committee on Powder Diffraction Standards (JCPDS). The IR spectra of calcium oxide appear at wavenumber 362 cm-1 which is characteristic of CaO vibration. Application of calcium oxide from Achatina fulica shell for synthesis of biodiesel from waste cooking oil results in biodiesel with density are in the range of ASTM standard.